Análise da influência de adição de óxido de nióbio nas propriedades de matrizes cimentícias - Cardoso, Marianna do Rocio (2021)
Brazil is the world`s largest holder of niobium reserves with about 98% of all the mineral on the planet. Despite this, a large part of the mineral is exported as raw material to other countries, due to the lack of investment in technology and development of products and applications for niobium at a national level. Thus, in order to stimulate and develop new applications for the promising mineral, this research analyzed the mechanical strength and the properties in the fresh and hardened state of cementitious matrices with the addition of 25. In the study, two stages were carried out, in the pilot project the optimum levels of niobium oxide were chosen based on the compressive strength at 7 days of curing. In this way, the contents of 0,5% and 5% of niobium oxide were chosen for the completion of the second stage, the experimental project. It was necessary to add a superplasticizer additive to improve the workability of the paste, due to the increase in the fines content of the mixture, since it was observed that as the addition of 25 increased, the fluidity of the mixture was reduced for the same content of superplasticizer additive. In terms of mechanical resistance, the content of 0,5% of 25 increased the compressive strength of the mixture at 7 days. Another analysed point was the reduction of the mass density of the paste in the fresh state, and the increase of the entrained air content with the increase of the addition, which is associated with the increase of the porosity of the matrix. Still, it was found that the niobium oxide accelerated the start time of setting of the cement paste, in addition to promoting a delay in the peak of the hydration heat release from the matrix. Moreover, there was an influence on the hydration heat accumulated during the hydration reactions, that showed a reduction when compared to the reference. Through the XRD test it was found out that the addition of 0,5% of the oxide lead to an increase in the formation of quartz during the reactions of the cement matrix. Finally, an increase in mass loss was observed in the thermogravimetric test with the addition of 25. Therefore, the present research offers a way for the use of niobium oxide in cementitious matrices.